Anatomy of a Wedding: Examining Religiosity, Feminism, and Weddings in GREY'S ANATOMY Anatomy of a Wedding - Sharon Lauricella (Journal for Religion, Film and Media, 2018)
Medical drama "Grey's Anatomy" features weddings as pivotal life events, with 14 unions portrayed over the program's 13 seasons on ABC. This paper is a synthetic approach combining communication, gender studies, and rigorous methodology to examine weddings in "Grey's Anatomy" through a feminist lens. We employ Butler's theory of gender performance and Rich's concept of compulsory heterosexuality to examine weddings throughout the show's extensive run. Depictions of women and weddings demonstrate dissonance between hegemonic gender performance and the potential to redefine the performance of "woman" in one's own ways. Tension exists between the program's portrayal of traditional heterosexual weddings and its progressive inclusion of a lesbian ceremony. We argue that the program's portrayal of both traditional "white" weddings and ceremonies which are more private and self-defined reflect the challenges inherent in navigating cultural expectations and personal objectives associated with performing as a "woman" in contemporary culture.